2020
DOI: 10.3389/fphar.2019.01659
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Polypharmacy in Adults 55 Years or Older: A Risk for Impaired Global Cognition, Executive Function, and Mobility

Abstract: Objectives: With their broad spectrum of action, psychotropic drugs are among the most common medications prescribed to the elderly. Consequently, the number of older adults taking multiple psychotropic drugs has more than doubled over the last decade. To improve knowledge about the deleterious effects of psychotropic polypharmacy, we investigated whether there is a threshold number of psychotropic molecules that could lead to impairment of global cognition, executive function, or mobility. Furthermore, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The prescription of antiacids (A02) is probably due to the association of obesity with gastroesophageal reflux [ 37 ], while the use of psychotropics (N05 and N06), antidiabetics (A10), and antithrombotics (B01) may be linked to the development of pathologies related to low PA. Specifically, it is encouraging to compare our results with those of Loggia et al [ 38 ], who found an independent association between psychotropic use and physical fitness (measured with the Timed Up and Go test).…”
Section: Discussionsupporting
confidence: 80%
“…The prescription of antiacids (A02) is probably due to the association of obesity with gastroesophageal reflux [ 37 ], while the use of psychotropics (N05 and N06), antidiabetics (A10), and antithrombotics (B01) may be linked to the development of pathologies related to low PA. Specifically, it is encouraging to compare our results with those of Loggia et al [ 38 ], who found an independent association between psychotropic use and physical fitness (measured with the Timed Up and Go test).…”
Section: Discussionsupporting
confidence: 80%
“…This fact is extremely important as some PIM may adversely affect cognition. Such cases should be closely followed up in order to understand whether their cognitive deficits are a consequence of neurodegenerative processes or were caused (or worsened) by any PIM [ 45 , 46 , 47 ]. On the other hand, the intake of these drugs helps to control neuropsychiatric symptoms, delirium episodes, aggressive behavior, and agitation, conferring protection to both the patient and the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to a sole antipsychotic prescription, antipsychotic-antidepressant-benzodiazepine combination therapy was associated with a 41% increased risk of mortality, and antipsychotic-benzodiazepine combination therapy was associated with a 119% increased risk of mortality in a registry-based sample (Nørgaard et al, 2020). Moreover, psychotropic polypharmacy has also been associated with cognitive and mobility impairment in community-dwelling adults without dementia (Loggia et al, 2020). To our knowledge, adverse effects of receiving psychotropic polypharmacy have yet to be examined in NH residents with dementia.…”
Section: Discussionmentioning
confidence: 99%